Laparoscopic cholecystectomy in patients with liver cirrhosis: review of intraoperative measures and recommendations - Abdelrahman, Tamer M. (International Surgery Journal, 2021)
Abstract Symptomatic biliary stones are related with higher morbidity and mortality rates in patients with liver cirrhosis, especially when patients undergo surgery. The difficulty of cholecystectomy is worsened by liver cirrhosis, especially in patients with extensive liver fibrosis and portal hypertension. Laparoscopic cholecystectomy can be performed safely in selected patients with cirrhosis. However, it can be challenging in many aspects and poses a greater degree of difficulty and thus should be performed by experienced surgical teams, who follow the recommendations and take in mined the special precautions which requested to increase safety of the operation and avoid or reduce the morbidity and mortality , and also who able to tackle the more frequent intraoperative incidents or complications. In this review, we focus on of the technical difficulties and intraoperative recommendations that could be used to approach laparoscopic cholecystectomy in this patient population (trocar placement, intraabdominal pressure, visualization, gallbladder dissection, adjunct for hemostasis, intraperitoneal drains, and conversion to open surgery), and the alternative which can be used in advanced cases